PP.10.13: LOW DIASTOLIC BLOOD PRESSURE AS A CARDIOVASCULAR RISK FACTOR IN ELDERLY HYPERTENSIVE SUBJECTS. (June 2015) - Hermida, A.; Lopez, J.E.; Alende, M.J.; Calvo, G.; Pose, A.; Calvo, C.
Abstract : Objective: The aim of this study was to identify cardiovascular risk factors in a cohort of hypertensive subjects over 70 years. Design and method: We designed a retrospective cohort study. The study population included 72 hypertensive patients over 70 years and they all underwent a complete annual medical examination from January 2011 to December 2014, including 48-hours blood pressure monitoring (ABPM) in order to exclude those with "white-coat" hypertension. They also underwent applanation tonometry to estímate central aortic blood pressure and carotid-femoral pulse wave velocity (PWV). Primary endpoint was the combination of fatal/non-fatal coronary heart disease or fatal/non-fatal stroke, or peripheral revascularization. All events were confirmed on the basis of medical records. Results: A total of 14 cardiovascular events were identified (6 fatal CV events, 3 acute coronary events, 3 acute congestive heart failure episodes and 2 ischemic strokes). There were not any differences between those subjects with or without any CV event regarding age, gender, body mass index, waist perimeter, office systolic/pulse pressure, central systolic BP or PWV. Both office and central diastolic BP were lower in those elderly hypertensive subjects with CV events (71.5 Vs 79.7 mmHg; p = 0.02 and 72.2 Vs 81.8 mmHg; p = 0.01, respectively). When taking into account 48-hour ABPM, we only found significant differences on pulse pressure, higher on those with CV events (67.4 Vs 59.6 mmHg). A multivariate analysis demonstrated that office dyastolic BP under 70 mmHg or central DBP under 75 mmHg were risk factor for the occurrence of fatal/non fatal CV events (RR: 1.78; 95%CI: 1.08–2.93 and RR: 1.57; 95%CI: 1.061–2.53, respectively). Conclusions: We conclude that those hypertensive subjects over 70 years with low office or central diastolic BP had worse cardiovascular prognosis. We suggest 70 mmHg as a valid diastolic BP treshold that below which survival is impaired.